Between Apollo and Osiris: Egyptianising East Greek Pottery, Translating Gods and Cross-Cultural Interaction in the 6th Century B.C. - Villing, Alexandra (Jahrbuch des Deutschen Archäologischen Instituts, 2022)
Relatively few Greek fine ware vessels have been uncovered in Egyptian contexts of the late 7th and 6th centuries B.C., the majority of East Greek production. Remarkably, though, the shape and imagery of a good number of them seem to reference local Egyptian customs and ideas, notably Osirian religion and regional sacred geographies, either representing them directly, or translating them into a Greek idiom. The vessels were probably commissioned by Greeks in Egypt from craftsmen in their homelands to be offered as bespoke containers to Egyptian sanctuaries and/or (religious) dignitaries. Their origins and distribution indicate two main networks of contact and exchange: one linking North Ionian Teos and Klazomenai with Thebes in the Nile valley, the other Rhodes with Daphnai and Memphis in the Nile Delta. Together with other evidence they suggest that Greeks from a wide social spectrum were acquiring a high level of intimacy with Egyptian culture. Ritual practice in particular emerges as a vital arena for Greek-Egyptian interaction and as a main conduit for elements of Egyptian culture to enter the wider Greek sphere.